Effect of gypsum and cow manure on yield, proline content, and K/Na ratio of soybean genotypes under saline conditions - Wiwin Sumiya Dwi Yamika; Nurul Aini; Adi Setiawan; Runik Dyah Purwaningrahayu (Brawijaya University, 2018)
Gypsum and cow manure potential as ameliorant to increase crop production under salt stress or saline condition. This research aimed to learn the effect of gypsum and cow manure on the uptake of Na, K and the yield of soybean genotypes under saline condition. This research conducted in green house Jatikerto Experimental Farm Faculty of Agriculture, Brawijaya University, from June to September 2014. The research was arranged in a split plot design. The main plot was soybean genotypes consists of two saline susceptible varieties (G1 = Wilis and G2 = Tanggamus) and two saline tolerant genotypes (G3 = genotype IAC, 100/Bur//Malabar and G4 = genotype Argopuro//IAC, 100); sub plot was ameliorant application consists of A0 = without ameliorant; A1 = cow manure (20 t/ha); and A2 = gypsum (5 t/ha). The results of the research showed that Leaf Chlorophyll Index in susceptible varieties and tolerant genotypes were increased with ameliorant application. Accumulation of proline and K/Na ratio in susceptible varieties higher than tolerant genotypes. Ameliorant application on tolerant genotypes increased grain yield higher than susceptible varieties